Analysis Of The Effect Of Corporate Social Responsibility And Corporate Governance Performance On Tax Avoidance With Profit Level As Moderation - Noor, Syaifullah; Darmansyah, Darmansyah; Rachbini, Widarto (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
This study discusses the influence of the performance of Corporate Social Responsibility and Corporate Governance on tax avoidance with a profit rate as a moderator during the 2014-2018 period of companies in agricultural sector and basic industry and chemical sectors listed on the Indonesia Stock Exchange. This study seeks to confirm similar studies in the USA and Indonesia that provide inconsistent results with one another related to earnings performance as a CSR moderation against tax avoidance, namely earnings performance strengthens the influence of CSR both when earnings are high or when they experience a decline. The results of this two previous study empirically give the impression that tax avoidance behavior is not influenced by the rate of profit, because it occurs when profits are high and when profits fall. The results of the study stated that CSR performance and the Proportion of Independent Commissioners have a positive effect on tax avoidance, and the Audit Committee has no effect on tax avoidance. While the Profit Level does not strengthen either the influence of CSR Performance, the Proportion of Independent Commissioners and the Audit Committee on tax avoidance.